Aging Induced p53/p21 in Genioglossus Muscle Stem Cells and Enhanced Upper Airway Injury. (4th March 2020) - Zhu, Lu-Ying; Yu, Li-Ming; Zhang, Wei-Hua; Deng, Jia-Jia; Liu, Shang-Feng; Huang, Wei; Zhang, Meng-Han; Lu, Yan-Qin; Han, Xin-Xin; Liu, Yue-Hua
Abstract : Aging of population brings related social problems, such as muscle attenuation and regeneration barriers with increased aging. Muscle repair and regeneration depend on muscle stem cells (MuSCs). Obstructive sleep apnea (OSA) rises in the aging population. OSA leads to hypoxia and upper airway muscle injury. However, little is known about the effect of increasing age and hypoxia to the upper airway muscle. The genioglossus (GG) is the major dilator muscle to keep the upper airway open. Here, we reported that muscle fiber and MuSC function declined with aging in GG. Increasing age also decreased the migration and proliferation of GG MuSCs. p53 and p21 were high expressions both in muscle tissue and in GG MuSCs. We further found that hypoxia inhibited GG MuSC proliferation and decreased myogenic differentiation. Then, hypoxia enhanced the inhibition effect of aging to proliferation and differentiation. Finally, we investigated that hypoxia and aging interact to form a vicious circle with upregulation of p53 and p21. This vicious hypoxia plus aging damage accelerated upper airway muscle injury. Aging and hypoxia are the major damage elements in OSA patients, and we propose that the damage mechanism of hypoxia and aging in GG MuSCs will help to improve upper airway muscle regeneration.